The Effect of Capital Structure on Profitability: Evidence from Companies Listed on Bursa Malaysia - Fong, Lai Kwin (2008)
The purpose of this paper is to study the effect of capital structure on profitability of Bursa Malaysia listed companies from the Industrial Products industry. Panel data of 93 companies from this industry, covering a six-year period, 2001-2006, is analysed. In contrast to previous empirical work on capital structure, this paper attempts to study the effect using panel data regression analysis and analyse the mixed evidence from previous studies. The relationships between the ratio of short-term debts and share capital, between long-term debts and share capital and between total debts and share capital are positive. However, the positive relationships are not significant. One of the factors that might affect the results is the exclusion of data from private companies. Public companies analysed in the study would have met the required threshold of paid-up capital and tack record. Thus, bank borrowings are not the main source of financing for public listed companies. Additionally, the financing intensity by the banking institutions has declined in the aftermath of the Asian financial crisis. Malaysian companies tend to depend on the capital market than debt financing and if debts are used, the proportion is lower as compared to share capital. Size emerged as a significant determinant factor of profitability. Hence, companies should focus on enlarging the size of their companies. This may be done by widening geographically presence or increasing types of products to increase market share and revenue. Keywords: Capital Structure, Profitability, Malaysia, Trade-off Theory, Agency Cost Theory, Pecking Order Theory, Panel Data Regression Analysis